Quizizz as an assessment media at EFL teaching: Students’ voices - Nada Bela Andresta; Choiril Anwar (EduLite: Journal of English Education, Literature and Culture, 2022)
This study aims to determine students' perceptions of using Quizizz as an English assessment medium. This study uses a descriptive qualitative method taken one month to collect data using close-ended questionnaire as the instrument. The sample used in this study was 3 classes in Grade 10 at SMA N 2 Semarang in the 2021/2022 academic year with a total of 108 students. From the data collection of the questionnaire distribution, it shows that 88.9% or 96 of students have positive perceptions and 5.6% or 6 of students have neutral perceptions, and 5,6% or 6 students have negative perceptions of the use of Quizizz as a medium for assessing English in their classes. It can be concluded that students in Grade 10 at SMA N 2 Semarang have a positive perception of the use of Quizizz. The students thought that the Quizizz media was a fun medium and very suitable to be used by teachers because the media was very interesting and practical to use for English assessment media.